PTH-139 Is There Nationwide Variation in the Proportion of Palliative Oesophago-Gastric Cancer Patients Dying in Hospital?. (17th August 2016) - Chadwick, G; Cromwell, D; ,
Abstract : Introduction: The DH 'End of Life Care Strategy' recommends that patients are treated in familiar surroundings and previous studies have suggested that 56–74% of people would prefer to die at home. 1 This study investigated whether there was nationwide variation in the proportion of palliative oesophago-gastric (OG) cancer patients dying in hospital. Methods: We used data from the National Oesophago-Gastric Cancer Audit to identify patients diagnosed with OG cancer in England and Wales between 1/4/2011 and 31/3/2013. The study was limited to patients managed with palliative intent who died during follow up. Place of death was identified by linking the data to the ONS death register. The proportions of patients dying in hospital were derived for each strategic clinical networks (SCNs), and were adjusted for regional differences in age, sex, planned modality, and social deprivation. Results: 22, 285 patients were diagnosed with OG cancer, 13, 187 were managed with palliative intent and 12, 012 of these died during follow up. Overall, 34.6% of patients died in hospital, 34.3% died at home, 18.5% died in a hospice, 10.9% died in a care home and 1.7% died elsewhere. After adjustment, the proportion of patients dying in hospital across SCNs typically fell between 30% and 40% (see Figure 1 ). The value of 50.9% (95% CI 46.1–56.0%)) for South Wales was large, in comparison. Conclusion: About one third of OG cancer patients treated palliatively die in hospital, and there was some variation between regions in England and Wales. This needs to be monitored at a local level, and investigated where rates are higher than expected. Differences between regions may reflect local access to hospice services and other social support. Reference: 1 National Audit Office (2008). End of life care. http://www.nao.org.uk/report/end-of-life-care/ Disclosure of Interest: None Declared